2017
DOI: 10.1161/jaha.117.007486
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impact of Serial Measurement of Nonplatelet Thromboxane Generation on Long‐Term Outcome After Cardiac Surgery

Abstract: BackgroundSystemic thromboxane generation, not suppressible by standard aspirin therapy and likely arising from nonplatelet sources, increases the risk of atherothrombosis and death in patients with cardiovascular disease. In the RIGOR (Reduction in Graft Occlusion Rates) study, greater nonplatelet thromboxane generation occurred early compared with late after coronary artery bypass graft surgery, although only the latter correlated with graft failure. We hypothesize that a similar differential association exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
0
1
Order By: Relevance
“…Poor agreement between test platforms has been reported previously in adult studies, including one where UTxB2‐based aspirin nonresponsiveness after ischemic stroke was more predictive for future major cardiovascular events than VN 3,16–18 . Early inflammatory‐induced (i.e., COX2‐associated) thromboxane production has been hypothesized as a major contributor to vascular complications after cardiac procedures due to its promotion of vasoconstriction and platelet aggregation, 18–20 though more studies have demonstrated its predictive value for long‐term major cardiovascular events 21–23 . The lack of thrombotic events in this pilot study did not allow determination of the relative predictive value of the two tests.…”
Section: Discussioncontrasting
confidence: 55%
“…Poor agreement between test platforms has been reported previously in adult studies, including one where UTxB2‐based aspirin nonresponsiveness after ischemic stroke was more predictive for future major cardiovascular events than VN 3,16–18 . Early inflammatory‐induced (i.e., COX2‐associated) thromboxane production has been hypothesized as a major contributor to vascular complications after cardiac procedures due to its promotion of vasoconstriction and platelet aggregation, 18–20 though more studies have demonstrated its predictive value for long‐term major cardiovascular events 21–23 . The lack of thrombotic events in this pilot study did not allow determination of the relative predictive value of the two tests.…”
Section: Discussioncontrasting
confidence: 55%